A Timing Correction Algorithm-Based Extended SVM for Three-Level Neutral-Point-Clamped MLI in Over Modulation Zone - Bharatiraja, C.; Jeevananthan, S.; Munda, Josiah L. (IEEE journal of emerging and selected topics in power electronics, 2018)
The space vector modulation readied multilevel inverter (MLI) has become palpable in industrial drives. The operation of voltage-source inverter drives in the overmodulation (OVM) mode is necessary as it patronages the extended speed range of the ac drives. This paper proposes a timing correction algorithm (TCA) to incorporate the OVM mode in space vector pulsewidth modulation (SVPWM) for the three-phase three-level neutral-point-clamped (NPC) MLI drive. First, the boundary restriction inherited in the hexagonal space vector diagram of linear modulation (LM) is redefined/quantified as modulation depth loss factor and computed for various values of modulation index belongs to the OVM region. Next, the appropriate time correction is carried out in the switching vector timings. The TCA insinuatingly corrects these magnitude gains and losses in terms of addition and subtraction of the corrective term in the on-time of the switches. The proposed timing corrected SVPWM strategy hosts a simple assessment and a duty-cycle recalculation procedure for determining on-times. This avoids the conventional nonlinear function and the lookup table. The proposed TCA-based SVPWM is simulated in LM and OVM regions using MATLAB/Simulink, and the corroboration is done using a field programmable gate array SPARTAN-III-3AN-XC3S400 architecture on 2-kW three-phase three-level NPC-MLI fed ac drive.